2005
DOI: 10.1002/chin.200603162
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Hepatic Transport of Strongly Fluorescent Cholephilic Dipyrrinones.

Abstract: Fused pyrimidine derivatives R 0515 Synthesis and Hepatic Transport of Strongly Fluorescent Cholephilic Dipyrrinones. -(WOYDZIAK, Z. R.; BOIADJIEV, S. E.; NORONA, W. S.; MCDONAGH, A. F.; LIGHTNER*, D. A.; J. Org. Chem. 70 (2005) 21, 8417-8423; Dep. Chem., Univ. Nev., Reno, NV 89557, USA; Eng.) -Lindner 03-162

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…17,18,20 Animal procedures, HPLC methods, and the provenance of the animals used also have been described in detail previously. 28 All animal studies were in compliance with institutional guidelines and approval requirements. For metabolism studies, each pigment (∼0.25 mg, accurately weighed on a microbalance) was dissolved in 0.1 mL of dimethyl sulfoxide (DMSO) or argon-degassed 0.1 M NaOH and the optically clear solution was slowly and quantitatively diluted into 1 mL of rat serum using a finely drawn out Pasteur pipet.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18,20 Animal procedures, HPLC methods, and the provenance of the animals used also have been described in detail previously. 28 All animal studies were in compliance with institutional guidelines and approval requirements. For metabolism studies, each pigment (∼0.25 mg, accurately weighed on a microbalance) was dissolved in 0.1 mL of dimethyl sulfoxide (DMSO) or argon-degassed 0.1 M NaOH and the optically clear solution was slowly and quantitatively diluted into 1 mL of rat serum using a finely drawn out Pasteur pipet.…”
Section: Methodsmentioning
confidence: 99%
“…Hydration and bile flow were maintained by infusion of a bile salt/lipid solution. 28 Bile was collected in 20-µL aliquots into glass tubes and flash-frozen immediately with dry ice, and bile flow rates were estimated gravimetrically. Frozen samples were stored at -70 °C pending HPLC analysis, when they were mixed with 80 µL of eluent and microfuged.…”
Section: Methodsmentioning
confidence: 99%
“…Bilirubin ditaurate (10) was from Frontier Scientific (Logan, UT) and di-n-octylamine from Sigma-Aldrich (St. Louis, MO). Animal procedures, sources of rats, and HPLC methods were as detailed elsewhere (Woydziak et al, 2005;McDonagh and Lightner, 2007). For biliary excretion studies, pigments (ϳ0.25 mg, accurately weighed), freshly dissolved in argon-degassed 0.1 M NaOH, were quantitatively diluted into 1 ml of rat serum.…”
Section: Methodsmentioning
confidence: 99%
“…4) that is taken up by unknown hepatic transport proteins and is excreted into bile by Mrp2 and an Mrp2-independent pathway. 16 The hepatobiliary disposition of this substrate was evaluated in automated SCRH studies, and results consistently showed significant accumulation (cells + bile = 180 ± 27 pmoles/mg protein; cells= 110 ± 9.2 pmoles/mg protein) and a relatively high BEI (41 ± 8.6) in SCRH (n = 6), which are both desirable probe quantities.…”
Section: Evaluation Of a Fluorescent Probe Using Scrhmentioning
confidence: 95%
“…[13][14][15] Sulfoglow 1a was selected as a novel substrate to evaluate with automated studies because it is a water-soluble, fluorescent molecule with some structural similarities to bilirubin, and it is rapidly taken up and excreted intact following intravenous injection into rats. 16 Bilirubin and its glucuronide conjugates are well-recognized markers of hepatic dysfunction. 17 Here, we demonstrate the use of the applications described above using SCRH in a fully automated format.…”
mentioning
confidence: 99%